Competitiveness of ecuadorian bananas with the use of cleaner technologies in cultivation - Quintana Rafael, Apolinario; Arias Edison, Olivero; Márquez Mariana, Alvarado (Revista Universidad de Guayaquil, 2015)
The aim of this project is to show that with the renewal of cleaner technology in the production of bananas, conditions for maintaining the health and quality of life in the soil increases. The methodology used is a qualitative approach using exploratory method with secundary information of governmental and non governmental institutions, and it demonstrated how important is the constant training for producers betting as always innovation in this particularly area, specially in organic thus being more competitive with other markets. Beyond all food benefits that has this fruit, there are drawbacks in production as the misuse of agrochemicals (pesticides) in production and low soil renewal, leading to resistant pests affecting the crop, putting in competitive disadvantage. Using traditional farming methods with better management of fertilizers or manure, ensuring that the plants are resistant, and thus the marketing of banana production certified as organic, will protect plantations against pests and diseases such as Black Sigatoka, following the certification standards and consumer protection foodstuffs and reducing environmental pollution.
Keywords: Banana export; quality; organic